(untitled) (Gaceta Técnica, 2025)
The seismic performance of a structural steel building designed using the Force Method (FDM) was compared with that of another using the Displacement Method (DDM) under the system of special moment-resistant frames in each microzone of the Barquisimeto-Cabudare Seismic Microzoning (SMM) ordinance. A regular archetype was established in plan and elevation, with four levels of 3 meters each, and three spans of 3 meters each for each analysis direction. The beams and purlins were IPE profiles, and the HEB columns were made of A36 steel grade with BFP beam-column connections. The results demonstrated that in SMM #1, the dimensions were established by the minimum requirements of the prequalified BFP connection for both methods, with identical seismic performance. For MSZ #2 and #5, the fundamental period of the structures coincided with the characteristic period of the soil, requiring more robust sections to avoid resonance and consequently obtaining identical earthquake-resistant behavior for both methods. In MZS #3, #4 and #6, both methods showed behavior close to yielding, but with less steel and story drifts when applying the MDD. MSZ #7 behaved similarly to the previous one, with the difference that the amount of steel was greater for the MDD. For MSZ #8 and #9, the MDD obtained behavior close to yielding, while in the MDF, the behavior was post-yielding with insignificant incursion into the inelastic range and repairable damage